Exploring various models of health coaching for improving blood pressure control among patients with hypertension attending primary health care settings: A scoping review - Arief Alamsyah; Fatwa Sari Tetra Dewi; Vita Yanti Anggraeni; Iqbal Sholahudin Maududdy (Malaysian Family Physician)
Introduction: This study aimed to explore various models of health coaching used for blood pressure control in patients visiting primary care settings, along with the underlying theories. Additionally, the study sought to identify individuals serving as health coaches and the effect of health coaching on blood pressure control and risk factors. Methods: This scoping review followed the PRISMA-ScR guidelines and utilised several databases including PubMed, ScienceDirect, ProQuest, Scopus and Web of Science. The search focused on articles published from January 2012 to July 2024. Eligible articles were examined to identify the forms of health coaching, the backgrounds and roles of health coaches and the outcomes of health coaching. Results: An initial search yielded 963 articles, of which 16 were selected for the review. Most studies (n=10) showed that health coaching was used in conjunction with other strategies (multicomponent). The most frequently applied approach was phone coaching (n=9). The majority of the interventions were completed within 6 months (n=4). Eight studies indicated that most health coaches came from health backgrounds including nurses, pharmacists and family doctors. Positive clinical outcomes, such as decreased systolic and diastolic blood pressures or systolic or diastolic blood pressure alone, were documented in all included investigations. The non-clinical outcomes varied. Conclusion: Health coaching is a promising approach for controlling blood pressure in primary care settings. This study highlights the importance of designing the form, time and staff for conducting effective health coaching in primary care settings.